femoropopliteal bypass graft above-knee five years’ experience in Tishreen university hospital in latakia techniques and results - سليمان محمود علي , (Latakia University Journal -Medical Sciences Series, 2023)
Arterial repair technique ( vein graft, prosthetic graft, endovascular….) varies according to each patient, each patient is a special case taking into consideration ( Quality of life , Clinical grade , Extension of atherosclerotic injury ) . Use of graft to repaire superficial femoral artery injury is a simple and repetitive technique in the surgical department. nevertheless, it is the subject of much debate and controversy. Long-term continuity of flow is better by using the venous graft than the artificial graft which should be used when the saphenous vein unusable or that it should be preserved for cardio bypass or vascular bypass below the knee. In this study (105 cases ), we examine the types of artificial grafts that were used in Tishreen university hospital in latakia in the period 2017-2022 and results for each type and compare that to global results.